Socio-technological influence on trust in artificial intelligence in digital agriculture - Attoungbre, Jeanne-Marie; Fritzsche, Albrecht (International Conference on AI and the Digital Economy (CADE 2024), 2024)
The paper investigates trust in artificial intelligence (AI) within socio-technological parameters to increase adoption of AI-based solutions in agriculture. Despite the benefits provided by AI-systems and the aforementioned trust factors, acceptance and the aforementioned trust factors, acceptance and adoption of AI-solutions have not been consistently observed, especially in agriculture. We employed qualitative research techniques conducting semi-structured interviews with experts from the agri-technology industry. Findings indicate variations in the level of trust in AI from one solution to another, depending on the design/appearance of the solution and how familiar it appears to farmers. Additionally, the importance of the social environment in building trust, particularly in circumstances of low general and technology knowledge, was highlighted. This research contributes to advancing our understanding of trust in artificial intelligence by providing insights from a social-technological perspective. On a practical level, the findings offer valuable insights to technology providers for designing and implementing their offerings.